Pengembangan Sistem VOIP Menggunakan Server Issabel Versi 4.0 dan Tunnel EOIP pada OMNI Hospital Alam Sutera - Elly Mufida; David Wardana Agus Rahayu (Universitas Bumigora, 2018)
The VoIP communication system at OMNI Hospital Alam Sutera uses the Elastix 2.5 server with the Centos 5.11 operating system. Elastix 2.5 by the developer has been declared End of Life. The server security system is a serious concern considering that VoIP servers can be accessed from the internet. Iptables and fail2ban applications are applications that are used to limit and counteract those who try to attack the VoIP server. One application that can be used as an open source VoIP server is the Issabel Application version 4.0. The migration process from Elastix 2.5 application to Issabel 4.0 by backing up all configurations in the Elastix 2.5 application through a web browser including the configuration of endpoints, fax, e-mail, asterisk. After the backup file is downloaded then upload the backup file to the Issabel 4.0 application then run the migration process. Adding a backup path as a failover connection is needed because the VoIP communication protocol between the OMNI Hospitals Group still uses one path so that when there is a problem in the connection path, the communication protocol will stop. The tunnel EoIP is a protocol used as a backup path between the OMNI Hospitals Group site.